Nudging the Mindset of Youth Out Migration from Kathmandu, Nepal - Munankami, Mahima; Agarwal, Riya; Rajbhandari, Samrat; Darnal, Manisha; Pote, Sibika (SAIM Journal of Social Science and Technology, 2024)
Purpose: This study explores the phenomenon of youth outmigration in Kathmandu, Nepal, focusing on the factors influencing their decisions within a globalized context. It addresses the challenges faced by Kathmandu's youth and the driving forces behind their migration. Design/Methodology/Approach: Utilizing a multiple regression model, the research examines variables such as employment opportunities, financial intentions, education, personal ambition, and government policies, with youth migration as the dependent variable. A comprehensive analysis employing a deductive approach and mixed-methods strategy was conducted, collecting data from a sample size of 77 respondents using convenience sampling techniques. Findings: The analysis reveals significant correlations between outmigration and factors such as employment opportunities, financial reasons, and education. Hypothesis testing confirmed the significant impact of these factors while rejecting the influence of personal ambition and government policy. Originality/Value: These findings offer valuable insights for policymakers and institutional leaders seeking to address youth migration in Kathmandu. They highlight the importance of informed decision-making in crafting effective interventions. This study contributes to the ongoing discourse on migration dynamics in urban centers and underscores the need for tailored strategies to retain talent and promote sustainable development. Despite limitations like sample size and potential data inaccuracies, the study provides valuable insights for policymakers to formulate targeted talent retention strategies, promoting sustainable growth in Kathmandu.